Effect of a Multidisciplinary Review Panel on Daily Morphine Milligram Equivalents for Patients With Chronic Pain - Glenn R. Kauppila; Sarah M. Strahm; Erica L. Vogel; Stephanie M. Raap; Dana H. Cash; Kaitlin J. Yost (SAGE Publishing, 2024)
Introduction/Objective: Physicians and other health care professionals are challenged regularly to balance managing pain for patients with chronic pain receiving chronic opioid therapy (COT) with following the national guidelines and standards regarding daily morphine milligram equivalents (MME). This quality improvement project aimed to determine the effect of referral to a multidisciplinary review panel on daily MME for patients receiving COT for chronic pain. Methods: This quality improvement project included patients who had an established relationship with a primary care or community internal medicine clinician at a large health care organization and were referred to a newly created multidisciplinary review panel for their recommendations regarding treatment of pain. Criteria for patient referral were diagnosis of a chronic, painful condition, and use of chronic opioid medications. These patients were selected and referred at the discretion of their primary care clinician from January 2, 2019, through December 31, 2020. Data for this project were collected at the time of initial referral to the panel and 6 months after recommendations. The daily MME were assessed at the 2 time points. Results: Thirteen patients were referred to the review panel during the project period. The median daily MME at the time of referral was 180. Daily MME decreased by a median of 14 MME after 6 months. The MME did not increase during the project period for any participants. Conclusions: Referral of patients receiving COT to a multidisciplinary review panel may reduce their daily opioid dose.